Women physicians in cardiovascular magnetic resonance: Past, present, and future - Sierra-Galan, Lilia M.; Aggarwal, Niti R.; Stojanovska, Jadranka; Raman, Subha V.; Han, Yuchi; Ferreira, Vanessa M.; Thomas, Katharine; Seiberlich, Nicole; Parwani, Purvi; Bucciarelli-Ducci, Chiara; Baldassarre, Lauren A.; Mavrogeni, Sophie; et al. (Frontiers in Cardiovascular Medicine, 2023)
Women’s engagement in medicine, and more specifically cardiovascular imaging and cardiovascular MRI (CMR), has undergone a slow evolution over the past several decades. As a result, an increasing number of women have joined the cardiovascular imaging community to contribute their expertise. This collaborative work summarizes the barriers that women in cardiovascular imaging have overcome over the past several years, the positive interventions that have been implemented to better support women in the field of CMR, and the challenges that still remain, with a special emphasis on women physicians.